Super-Refractory Status Epilepticus: An Atypical Presentation and Case-Based Review - Chiazor Udochukwu ONYIA; Morenikeji A. KOMOLAFE; Ayo M. ADEBIYI; Olusegun OYEWOLE; Fola A. FAPONLE (Archives of Epilepsy, 2015)

(untitled)
Super-refractory status epilepticus is known to typically arise either from a distinct underlying cause or, in patients with no history of epilepsy, from no overt cause. It has recently presented in an unclear pattern, and thus there are various challenges in its management in resourcepoor settings. This case report presents a recent experience and lessons learned from a case of super–refractory status epilepticus preceded by atypical features in a 50-year-old Nigerian woman, and briefly reviews the current concepts in management of this epilepsy, especially in the context of resource-poor settings. Super-refractory status epilepticus can present with a confusing clinical picture. A good outcome in the management of this difficult problem is highly dependent on accurate diagnosis and prompt treatment. In view of the difficulties resource–poor countries have in accessing the resources and facilities required for optimal care of patients with super–refractory status, any future treatment protocols should allow for the provision of readily available therapy options in such settings.